Protecting the State's National Security in Light of the Provisions of Naturalization - Boukharouba, Hamza (Journal of Legal Studies and Researches, 2022)
Naturalization sometimes causes fears in the receiving country. This calls for the enactment of a set of laws to ensure trust and confidence towards the foreigner who requests the nationality and at the same time, one can preserve the national security. This is the reason why the Algerian legislator has established through the Articles 10 and 11 of the Nationality Law a set of conditions that aim at achieving those goals.